The Neuroendocrine Functions of the Parathyroid Hormone 2 Receptor - Dobolyi, Arpad; Dimitrov, Eugene; Palkovits, Miklos; Usdin, Ted B. (Frontiers in Endocrinology, 2012)
The G-protein coupled parathyroid hormone 2 receptor (PTH2R) is concentrated in endocrine and limbic regions in the forebrain. Its endogenous ligand,tuberoinfundibular peptide of 39 residues (TIP39), is synthesized in only 2 brain regions, within the posterior thalamus and the lateral pons. TIP39-expressing neurons have a widespread projection pattern, which matches the PTH2R distribution in the brain. Neuroendocrine centers including the preoptic area, the periventricular, paraventricular, and arcuate nuclei contain the highest density of PTH2R-positive networks. The administration of TIP39 and an antagonist of the PTH2R as well as the investigation of mice that lack functional TIP39 and PTH2R revealed the involvement of the PTH2R in a variety of neural and neuroendocrine functions. TIP39 acting via the PTH2R modulates several aspects of the stress response. It evokes corticosterone release by activating corticotropin-releasing hormone-containing neurons in the hypothalamic paraventricular nucleus. Block of TIP39 signaling elevates the anxiety state of animals and their fear response, and increases stress-induced analgesia. TIP39 has also been suggested to affect the release of additional pituitary hormones including arginine vasopressin and growth hormone. A role of the TIP39-PTH2R system in thermoregulation was also identified. TIP39 may play a role in maintaining body temperature in a cold environment via descending excitatory pathways from the preoptic area. Anatomical and functional studies also implicated the TIP39-PTH2R system in nociceptive information processing. Finally, TIP39 induced in postpartum dams may play a role in the release of prolactin during lactation. Potential mechanisms leading to the activation of TIP39 neurons and how they influence the neuroendocrine system are also described. The unique TIP39-PTH2R neuromodulator system provides the possibility for developing drugs with a novel mechanism of action to control neuroendocrine disorders.